NUMBER OF OPERATIVE ACTIONS AND REFERRALS TO GYNECOLOGY CASES AT MALINGPING HOSPITAL 2020-2022 - William Halim (Riviera Publishing, 2024)
Almost every woman has experienced a gynecological condition in her life. Access to quality and adequate health services for women is one of the Indonesian government's national programs. The main aim of this study is to assess the number of procedures and referrals for gynecological cases at the Malingping Regional General Hospital (RSUD) from 2020 to 2022. This research is a retrospective descriptive study. The target population includes all gynecology patients in outpatient clinics. In contrast, the accessible population is all gynecology patients undergoing outpatient treatment at Malingping District Hospital during that period. Research shows that ovarian tumors dominate with 45% of a total of 140 cases, with various treatments such as surgery and referral, especially in cases of suspected malignancy. Malingping District General Hospital faces significant obstacles in patient referral, particularly in cancer cases involving long travel and long waiting times, which have the potential to worsen patient morbidity and mortality. Challenges such as limited anatomical pathology facilities, distance to referral hospitals, and the uneven distribution of specialist doctors underscore the need to improve infrastructure, services, and health policies to ensure better access for regional patients. Cases with gynecological problems can be managed observationally, medically, and operatively. Correct diagnosis is essential for successful treatment. Hospitals must have a unified system, human resources, facilities, and infrastructure to support this. The current problem at Malingping Regional Hospital is supporting examinations, the availability of which depends on the hospital's spending capacity.